Managing complexity in healthcare - Kuhn, Lesley, 1952-; Le Plastrier, Kieran (New York : Routledge, 2023)
Managing Complexity in Healthcare introduces the ComEntEth (Complex Entropic Ethical) model as an integrated bio-medical and philosophical approach to understanding how people get things done in healthcare. Drawing on the complexity sciences, studies of entropy in living organisms and the ethics of Emmanuel Levinas, healthcare is theorised as energetic relational exchanges between people as entropic and ethical entities that unfold around a central attractor: Reduction in elevated entropy or suffering in patients. Living entities are engaged in a continuous struggle against the tendency to produce entropy. From the cellular to the collective of human endeavours, the tendency of complex systems is to disorder and decay. Yet in the micro-activity of healthcare enterprise, people resist this tendency by expending energy to create order and sustain life. Making sense of how this miraculous work is made possible is the foundation of this book. Through practical examples - from analysis of practitioner burnout, rural and remote healthcare, the functioning of emergency departments, to government, social and institutional responses to the COVID-19 pandemic - this new integral philosophy provides practitioners, managers, policy designers, and scholars an effective way to understand the dynamics of daily processes and practices that link the micro of everyday interactions with the macro-trends of healthcare.
"Routledge Focus"
OCLC-licensed vendor bibliographic record.
Keywords: Health services administration; BUSINESS & ECONOMICS / Management